Does the sequence of plyometric and dynamic stretching exercises influence subsequent sprint performance? A randomized crossover intervention study - Silva, Devisson S.; Boullosa, Daniel; Pereira, Erika V. M.; Alves, Micael D.J.; Fernandes, Matheus S.S.; Aidar, Felipe; dos Santos, Leila F.; de Souza, Raphael F. (Biology of Sport, 2024)
The objectives of this study were to evaluate the acute effects of the sequence order of drop jumps (DJ) and dynamic stretching (DS) on sprinting performances in competitive athletes and to investigate the relationships between post-activation performance enhancement (PAPE) in sprint performance and lower limb power. Thirteen male jumpers and sprinters participated in this study (19 ± 2 years; 177 ± 7 cm; 71.7±5.6 kg). Through a randomized crossover design, the athletes were exposed to three different conditions after a standardized warm-up: DS+DJ, DJ+DS, and control. Sprinting performance over 40 m was analysed with consideration of initial (0 to 20 m) and final acceleration (20 to 40 m) phases. The effect of intervention was examined by two-way repeated-measures of ANOVA. Pearson’s correlation test was used to determine the association between PAPE during sprinting and jump performance. There was no effect of any factor on 40-m sprint performance. Meanwhile, the performance at 20–40 m was higher after the DS+DJ condition when compared to baseline (8.79±0.43 vs. 8.91±0.35 m/s; p = 0.015). However, the initial acceleration was worsened in the DJ+DS condition when compared to baseline (6.26±0.25 vs. 6.22±0.26 m/s; p = 0.002). There was a negative correlation between CMJ height and the improvement in final acceleration ( r = -0.741; p = 0.004). The use of DS prior to DJ is an effective strategy to improve performance in the final acceleration phase (20–40 m). The athletes with lower levels of lower limb power benefited the most from this PAPE strategy.